PEMBUATAN VIDEO PEMBELAJARAN ANIMASI 2D LAPISAN BUMI DAN TATA SURYA MATA PELAJARAN IPA KELAS VII (Studi Kasus : SMP Negeri 1 Tamansari) - Yudhi Hariyanto; Widiyanto Hadi; Febrianta Surya Nugraha (Jurnal Riset Sistem dan Teknologi Informasi, 2023)
Multimedia in the field of education is very closely related. The use of multimedia as a support and means of education is widely applied in accordance with the needs of the world of education. One of the multimedia fields that can be applied at the educational level is animation. 2D animation utilizes the resulting images from depicting objects or characters in each frame which are then arranged in the right order to create the illusion of movement. Here the researcher takes a case study in the subject of Natural Sciences (IPA) which focuses on the material of the earth's layers and the solar system. Based on the results of interviews conducted by researchers with the subject teachers concerned, many students experienced difficulties in understanding and even memorizing the material. This resulted in the scores obtained by students in science subjects, especially for the material on the layers of the earth and the solar system, to be low and below the Minimum Completeness Criteria (KKM), with the KKM score for science subjects on this material having a score of 70/100 and most students having value is still below 70/100. The flow of research conducted consists of the stages of data collection, analysis, and design. The resulting 2-dimensional animated video consists of 2 main materials, namely the layers of the earth which consist of the atmosphere, lithosphere and hydrosphere and the solar system.